The effect of digital banking adoption and risk management on bank performance: The intervening role of balanced scorecard - Irawan, Tedhi; Isa, Che Ruhana; Alfan, Ervina (International Journal of Innovative Research and Scientific Studies, 2025)
This research examines the effect of digital banking adoption and risk management on bank performance. In addition, this study examines the function of a balanced scorecard in mediating the impact of digital banking adoption and risk management on bank performance. The research was conducted using a survey questionnaire and a hypothetico-deductive approach, placing this in a positivist paradigm. Data were gathered from 200 senior bank managers in 40 banks, comprising 4, 16, and 20 state-owned, regional development, and private-owned banks, respectively. Meanwhile, data analysis and hypothesis testing were performed using the Structural Equation Model – Partial Least Square (SEM-PLS). The results revealed that digital banking adoption, risk management, and balanced scorecards directly and significantly affected bank performance. In addition, digital banking adoption enhanced risk management, and the balanced scorecard mediated the impact of digital banking adoption and risk management on bank performance. The research offers strategic insights for stakeholders such as banks and regulators on the factors influencing their performance in the digital era. Further, the study emphasizes the need for banks to systematically integrate their digital banking adoption and risk management considerations into their strategic planning and performance measurement processes.